2018
DOI: 10.1016/j.drugalcdep.2017.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Cigarillo sales in legalized marijuana markets in the U.S.

Abstract: Cigarillo product characteristics traditionally associated with blunt use may shape the tobacco market in legal marijuana regions. As more states continue to legalize recreational marijuana, state and local governments should anticipate the potential impact on the tobacco marketplace and implement tobacco control policies (e.g., flavor bans, minimum pack sizes) that discourage product use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 20 publications
(33 reference statements)
0
17
0
Order By: Relevance
“…Unlike an LCC, which has a tobacco filler, a blunt wrap consists of rolling paper made from tobacco leaf. While the blunt wrap composed only 2.8% of the U.S. cigarillo market in 2016 (Giovenco et al, 2018), the product was sold by more than half of the tobacco retailers in California who carried LCCs (Henriksen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike an LCC, which has a tobacco filler, a blunt wrap consists of rolling paper made from tobacco leaf. While the blunt wrap composed only 2.8% of the U.S. cigarillo market in 2016 (Giovenco et al, 2018), the product was sold by more than half of the tobacco retailers in California who carried LCCs (Henriksen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…There are only two studies to our knowledge, both cross-sectional, that have investigated the association between cannabis laws and the retail sales or availability of tobacco products used for blunt smoking (Giovenco et al, 2018;Lipperman-Kreda et al, 2014). Lipperman-Kreda et al (2014) reported a positive association between tobacco availability and laws permitting medical cannabis dispensaries in California jurisdictions.…”
Section: Introductionmentioning
confidence: 99%
“…[2] Cigar products are appealing because they come in flavors, often cost less than cigarettes, and can be used for marijuana consumption. [3] The term 'cigar' represents a specific class of products in which the tobacco is wrapped in tobacco leaf or another tobaccocontaining substance. [4] There are three broad classes of cigars: cigarillos, traditional cigars, and filtered cigars.…”
Section: Introductionmentioning
confidence: 99%
“…[5,6] Cigarillos are mid-sized, often used for marijuana consumption, and half of users purchase singles, which in 2013, cost approximately $1.15 each. [3,7] Traditional cigar users are typically older, White, and have higher incomes, and few report daily use. [5,6] Traditional cigars cost approximately $1.30 per cigar, and almost half of users purchase singles.…”
Section: Introductionmentioning
confidence: 99%
“…Following medical marijuana legalization in several U.S. states, there were significant increases cardiac mortality rates [29], but there were concurrent reductions in the rates of opioid prescribing, particularly in areas where cannabis dispensaries were legal. However, in these states, there was a concurrent increase in tobacco sales [30]. Compliance rates among chronic pain patients who were treated with opioids did not change following legalization in select U.S. states [31].…”
Section: Resultsmentioning
confidence: 99%